Geo-Archaeological study and cadaste detection using soft-computing techniques. - Evelpidou, N.; Vassilopoulos, A.; Rizakis, A.; Verikiou, E. (Atlas historique des cadastres d' Europe II, 2001)
This study is an attempt of creating a virtual model of Patra’s cadastre grid. For this purpose geomorphological and environmental data in combination to archaeological data were analysed using different information technologies. Different kinds of techniques were used in order to reach the target. Remote Sensing and Digital image processing was used in the first place to initiate the primary data. Geographical Information Systems (G.I.S.) were used for the processing of primary data and the production of secondary information layers. Geomorphological and environmental data were particularly helpful for the elimination of those lines that couldn’t be part of a Roman cadastre grid.